Effect of Active and Passive Function of the Posterosuperior Rotator Cuff on Compensatory Muscle Loads in the Shoulder. Issue 5 (23rd May 2022) - Moroder, Philipp; Chamberlain, Aaron; Gabriel, Stefan M.; Jacofsky, Marc C.; Sengun, Mehmet Z.; Spenciner, David B.; Tokish, John M.; Lacheta, Lucca
Background: Irreparable posterosuperior rotator cuff (PSRC) tears have been shown to result in shoulder pain and loss of function. Purpose/Hypothesis: The purpose of this study was to determine the effect of the loss of active or passive function of the PSRC on compensatory muscle loads in the deltoid and the remaining rotator cuff. It was hypothesized that both deactivation and resection of the PSRC would result in load increases in the remaining muscles and that resection of the PSRC would result in even higher required compensatory forces than would mere deactivation. Study Design: Controlled laboratory study. Methods: A total of 7 cadaveric shoulders were tested using a biomechanical shoulder simulator with 10 independently controlled actuators for various muscles (anterior, middle, and posterior deltoid; inferior and superior subscapularis; latissimus dorsi; pectoralis major; teres minor; supraspinatus; and infraspinatus) and 3-dimensional motion tracking. The muscle loads representing the latissimus dorsi and pectoralis major were each held constant, and the remaining muscle actuator forces required to abduct the arm in the scapular plane were determined. The actuator forces corresponding with arm elevation from 20° to 65° were compared at 5° increments for 3 testing conditions: (1) intact, active PSRC; (2) intact, deactivated PSRC; and (3) resected PSRC and shoulder capsule. Results: In both the deactivated and resected states, the teres minor showed a significant increase in required muscle forces through nearly the entire tested range of arm elevation compared to the active state. This was also the case for the subscapularis but only at higher elevation angles. The deltoid demonstrated increased muscle forces of at least 1 of its subunits between 25° and 55° of elevation when comparing the deactivated state or resected state to the active state. However, through nearly the entire range of elevation, no statistically significant differences were found between the deactivated and resected states for any of the actuator loads representing muscle forces. Conclusion: The loss of active function of the PSRC led to compensatory loads on the remaining rotator cuff and deltoid, regardless of the passive presence of the PSRC as a supposed subacromial spacer. Clinical Relevance: The findings encourage the exploration of treatment procedures that mimic the active function of the PSRC when the rotator cuff itself is irreparable.